A multichannel superconductor-based photonic crystal optical filter tunable in the visible and telecom windows at cryogenic temperature (2022)
We design and evaluate the performance of a one-dimensional photonic crystal (PhC) optical filter that comprises the integration of alternating layers of a barium titanate ferroelectric (Formula presented.) and an yttrium oxide dielectric (Formula presented.), with a critical high-temperature superconductor defect, yttrium–barium–copper oxide (Formula presented.), resulting in the (Formula presented.) (Formula presented.) multilayered nanostructure array. Here, we demonstrate that such a nanosystem allows for routing and switching optical signals at well-defined wavelengths, either in the visible or the near-infrared spectral regions—the latter as required in optical telecommunication channels. By tailoring the superconductor layer thickness, the multilayer period number N, the temperature and the direction of incident light, we provide a computational test-bed for the implementation of a PhC-optical filter that works for both wavelength-division multiplexing in the 300–800 nm region and for high-Q filtering in the 1300–1800 nm range. In particular, we show that the filter’s quality factor of resonances Q increases with the number of multilayers—it shows an exponential scaling with N (e.g., in the telecom C-band, (Formula presented.) for (Formula presented.)). In the telecom region, the light transmission slightly shifts towards longer wavelengths with increasing temperature; this occurs at an average rate of 0.25 nm/K in the range from 20 to 80 K, for (Formula presented.) at normal incidence. This rate can be enhanced, and the filter can thus be used for temperature sensing in the NIR range. Moreover, the filter works at cryogenic temperature environments (e.g., in outer space conditions) and can be integrated into either photonic and optoelectronic circuits or in devices for the transmission of information.